Exploring Nondeliberative Practice through Recreational, Art, and Music-Based Activities in Social Work with Groups. Issue 2 (2nd April 2016) - Kelly, Brian L.; Doherty, Lauren
ABSTRACT: This article reviews the history of recreational, arts, and music-based activities in social work with groups, providing a nondeliberative practice context. The article begins with an overview of nondeliberative practice, then presents various uses of recreational, art, and music-based activities during the Settlement House and Recreational Movements, in mid-20 th -century group work practice and in present practice. The article concludes with a review of current projects in the Chicago land area and highlights their potential to decrease young person on young person violence.